Effects of zeolite inclusion in aflatoxin B1-contaminated diet on the performance of laying duck - Sumantri, I.; Herliani, H.; Rajibi, A. N.; Edriantina, R. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
The researchwas objected to study the effect of zeolite inclusion in aflatoxin B1 (AFB1) contaminated diet on the performance of laying duck. A completely randomized design was adopted in the in vivo experiment that consisted of 4 treatments, namely: (1) commercial feed (Control); (2) AFB1-contaminated feed 70 ppb (AFC); (3) Control + 2% zeolite; and (4) AFC + 2% zeolite. Each treatment had 4 replications with 4 ducks in each replication. A total of 64 eight months-female Alabio duck (Anas platyrinchos Borneo) were used in 28 days of the feeding experiment. Data were analyzed according to the general linear model of SPSS 21.0 statistical software. Results indicated that AFB1 exposure significantly (P<0.05) decreased the body weight of laying duck by 1.12%. Zeolite inclusion could prevent the adverse effect of AFB1 on body weight that increased by 2.95% in AFC+2% zeolite. Treatments had no significant effect on egg production and egg weight (P>0.05). Zeolite inclusion resulted in the highest final body weight whilst AFB1 diet without zeolite resulted in the lowest final body weight (P<0.05). Relative liver weight of duck fedAFC diet was 16.62% and to be 15.4% by zeolite addition in the diet. In conclusion, 2% of zeolite inclusion could reduce the adverse effects of AFB1 exposure on the performance of laying duck.